Online self-presentation and emotional well-being among emerging adults in Malaysia: the mediating role of online friendship quality - Avethra, Muthu Pandian; Cheong, Wan Ning; Lee, Sue Qin (2021)
The evolution of the Internet increases social media usage and broadens the opportunity to develop new friendships online. The online world provides individuals with a platform to manifest their identity and self-presentation. Individuals are more willing to show their true selves to strangers online compared to face-to-face offline communication. This study examined the association between online self-presentation (adaptable self, authentic self, and freedom of self online) and emotional well-being (positive and negative affect) among emerging adults in Malaysia, online friendship quality as mediator. A correlational cross-sectional research design was used to collect quantitative data. A sample of 340 participants (74.9% females and 25.1% males) were collected using the purposive sampling method through the distribution of Qualtrics survey form online. Findings showed adaptable self and freedom of self online positively associated with online friendship quality. Adaptable self found positively linked to negative affect while authentic self negatively associated with negative affect. Online friendship quality was also found to be positively associated with positive affect. Besides, only online friendship quality mediates the linkage between freedom of self online and positive affect. Hence, this research is beneficial to the individual, society, and healthcare practitioner on increasing the awareness of self-presentation and online friendship quality with emotional well-being.